INTEGRATING MATHEMATICS LOCAL WISDOM BASED THROUGH WORKSHEET IN BILINGUAL PROGRAM - Nur Hidayanti; Melinda Yanuar; Ina Rohiyatussakinah (Journal Of Educational Experts (JEE), 2020)
Elementary school mathematics learning is generally taught classically by teachers. By using the lecturing method and the material is also general nationally. There is no regional element (local wisdom values) there is no technological element. In this study, researchers discussed the integration of local wisdom-based mathematics learning through the development of student worksheets with Banten culture in the bilingual program at the SDIT Assa'adah Global Islamic School (AGIS) Elementary School, Serang City. The aimed of this research is to introduce Banten regional culture to elementary school students in a bilingual program with Indonesian and English trough mathematic worksheet. Researchers also simultaneously introduce foreign languages that are commonly used. This study used Research and development in the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) method. the population of research are IT AGIS Elementary School students, and the sample is grade 4 SD IT AGIS. In this study, researchers drafted a grade 4 bilingual mathematics worksheet. The results were validated by 3 experts recommended worthy of being tested on students.